Linking Online Gaming and Addictive Behavior: Converging Evidence for a General Reward Deficiency in Frequent Online Gamers - Hahn, Tim; Notebaert, Karolien Hilde; Dresler, Thomas; Kowarsch, Linda; Reif, Andreas; Fallgatter, Andreas J. (Frontiers in Behavioral Neuroscience, 2014)
Millions of people regularly play so-called Massively Multiplayer Online Role Playing Games (MMORPGs). Recently, it has been argued that MMORPG overuse is becoming a significant health problem worldwide. Symptoms such as tolerance, withdrawal and craving have been described. Based on behavioral, resting state and task-related neuroimaging data, we test whether frequent players of the MMORPG “World of Warcraft” (WoW) – similar to drug addicts and individuals with an increased risk for addictions – show a generally deficient reward system. In frequent players of the MMORPG “World of Warcraft” (WoW-players) and in a control group of non-gamers we assessed 1) trait sensitivity to reward, 2) BOLD responses during monetary reward processing in the ventral striatum and 3) ventral-striatal resting state dynamics. We find a decreased neural activation in the ventral striatum during the anticipation of both small and large monetary rewards. Additionally, we show generally altered neurodynamics in this region independent of any specific task for WoW players (resting state). On the behavioral level, we found differences in trait sensitivity to reward, suggesting that the reward processing deficiencies found in this study are not a consequence of gaming, but predisposed to it. These findings empirically support a direct link between frequent online gaming and the broad field of behavioral and drug addiction research, thus opening new avenues for clinical interventions in addicted gamers and potentially improving the assessment of addiction-risk in the vast population of frequent gamers.